Considerations on the design of space structures - Active design and inclusion of nonlinear effects - Toklu, YC (Amer Soc Civil Engineers, 2004)
Two approaches that should be important in designing space structures are discussed active design in contrast to passive design, and consideration of nonlinear effects in contrast to being limited by linearity. It is stressed that use of these approaches will result in safer and lighter structures.
9th Biennial International Conference on Engineering, Construction and Operations in Challenging Environment -- MAR 07-10, 2004 -- League City Houston, TX